Articulate Storyline Application: Development of Foreign Language Learning Media on the Aspects of Listening Skills - Rokhim, Minatur; Oktaviani , Fina Mega; Safii, Randi (Language Development Center, 2023)
Background: Arabic learning media using the Articulate Storyline application has not been developed much to improve listening skills. Objective: This study aims to develop one of the Arabic learning media that can improve listening proficiency through the use of the Articulate Storyline application in Madrasah Tsanawiyah students. Method: This research uses the RnD method. The development model follows Dick and Carry's opinion with the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. Data collection procedures are obtained through, observation, interviews, questionnaires, and tests. The research instrument uses questionnaires. The source of data was obtained from an Arabic teacher, 20 students, and 3 experts. Data analysis techniques use descriptive analysis in percentage form using a paired sample t-test formula. Distribution of questionnaires to students and provision of tests in the form of pre-tests and post-tests. Each test has 20 questions. Researchers conducted a normality test using the Kolmogrof-Simirnov test one sample test. For quantitative data response questionnaires, presentations were processed using Likert scales (4) Very good, (3) Good, (2) Sufficient, and (1) less. Results and Discussion: The results showed that the Arabic learning media based on the Articulate Storyline application was declared very good, and could increase students' interest in learning. This is based on: (1) an Assessment of material experts with a percentage of 97% of criteria and Very feasible and an Assessment of media experts with a percentage of 75% of feasible criteria. (2) Student assessment through response questionnaires, obtained a percentage of 94% so that it is classified as very feasible criteria. (3) Pretest, obtained an average score of 56.80% in the sufficient category, post-test test 85% in the eligible category. Conclusion and Implication: The conclusion of this study shows that articulate storyline learning media can be accepted by students and teachers as Arabic learning media that can be a solution to the problem of learning listening skills at the Madrasah level. The implication of the research is that application-based media articulate storyline is one of the best tools needed in learning foreign languages and improving language proficiency.